Pembelajaran Seni Musik Materi Bernyanyi Solo Kelas VII SMPN 30 Padang - Alfadli, Sarah; Jagar Lumbantoruan (EDUMUSIKA, 2024)
This study aims to determine and describe the Implementation of Music Learning Solo Singing Material in class VII SMP N 30 Padang. This type of research is qualitative, with a descriptive approach. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery, cameras and cellphones. Data collection techniques are done through literature study, observation, interviews and documentation. Data analysis techniques are collecting data, classifying data, clarifying data, analyzing data, describing, and concluding data. The results showed that teachers did not fully understand the 7 stages of planning in accordance with the standard criteria of the independent curriculum. The impact of the conditions, at the stage of implementing learning has not been carried out properly, the teacher's teaching methods and strategies have not been implemented properly in accordance with the achievements and learning flow based on the independent curriculum. Teachers who are too focused on teaching only by explaining the material and the lack of practical action in the implementation of learning with solo singing material. Furthermore, at the practical stage of taking grades, the teacher does not assess students' abilities based on good and correct solo singing standards, but only by the courage of students to come forward the teacher has given value to this. And the teacher also does not carry out enrichment or remedial from the results of taking the solo singing practice score, this causes that the formative assessment has not been carried out as a measuring tool to determine the achievement of students' solo singing learning outcomes in the implementation of learning.